Three-dimensional kinematic analysis and power output of elite flat-water kayakers - Bjerkefors, A.; Tarassova, O.; Rosén, J. S.; Zakaria, P.; Arndt, A. (Sports Biomechanics, 2018)
The purpose was to examine power output and three-dimensional (3D) kinematic variables in the upper limbs, lower limbs and trunk in elite flat-water kayakers during kayak ergometer paddling. An additional purpose was to analyse possible changes in kinematics with increased intensity and differences between body sides. Six male and four female international level flat-water kayakers participated. Kinematic and kinetic data were collected during three tasks; low (IntL), high (IntH) and maximal (IntM) intensities. No differences were observed in any joint angles between body sides, except for shoulder abduction. Significantly greater range of motion (RoM) values were observed for IntH compared to IntL and for IntM compared to IntL in trunk and pelvis rotation, and in hip, knee and ankle flexion. The mean maximal power output was 610 ± 65 and 359 ± 33 W for the male and female athletes, respectively. The stroke frequencies were significantly different between all intensities (IntL 59.3 ± 6.3; IntH 108.0 ± 6.8; IntM 141.7 ± 18.4 strokes/min). The results showed that after a certain intensity level, the power output must be increased by other factors than increasing the joint angular RoM. This information may assist coaches and athletes to understand the relationship between the movement of the kayaker and the paddling power output.. ABSTRACT FROM AUTHOR